2016
DOI: 10.4103/0976-7800.191020
|View full text |Cite
|
Sign up to set email alerts
|

An aggressive angiomyxoma of vulva - A rare entity - A case report

Abstract: Aggressive angiomyxoma is a rare, locally invasive mesenchymal tumor predominantly presenting in women of reproductive age and also having a moderate-to-high risk for local relapse. Hence, it needs to be differentiated from other mesenchymal tumors occurring in this region. We present here a case of a 40-year-old female presenting with a large, fleshy, pedunculated mass on the right labia majora.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…However, the ratio of occurrence in females to males is 6:1. 8 Aggressive angiomyxoma may be commonly misdiagnosed as angiomyofibroblastoma. However, the latter is well circumscribed, more cellular, and more vascular.…”
Section: Discussionmentioning
confidence: 99%
“…However, the ratio of occurrence in females to males is 6:1. 8 Aggressive angiomyxoma may be commonly misdiagnosed as angiomyofibroblastoma. However, the latter is well circumscribed, more cellular, and more vascular.…”
Section: Discussionmentioning
confidence: 99%
“…Occasionally, they are seen in male patients in related sites like the scrotum and inguinal region. However, the ratio of occurrence in females to males is 6:1 [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are currently no guidelines for the postoperative follow-up. However, according to Das et al, patients should be followed for at least 15 years with yearly physical exams and potentially with MRI to rule out recurrence [9]. Some studies have shown benefit with preoperative treatment by radiation therapy or hormonal antagonists such as GnRH agonists in order to shrink the tumor to avoid extensive resection [1,2].…”
Section: Discussionmentioning
confidence: 99%